Application of Project Based Learning Model Assisted by Animated Video Media to Improve Student Learning Outcomes in Grade V Elementary School Elementary School - Utami, Sri; Gagaramusu, Yusdin Bin.M.; Rahmah, Nur; Azizah, Azizah; Nuraini, Nuraini (Journal of Educational Sciences, 2025)
This research aims to improve student outcomes by applying a project-based learning model assisted by animation video media in the Science Class V subject of SD Alhairaat Tondo. The research method used is class action research, which refers to the diagram presented by Kemmis and Mc Taggart. Based on the results of the research on the application of the project-based learning model assisted by animation video media to improve student learning outcomes in the Science Class V subject of SD Alkhairaat Tondo, this is shown by the percentage of student learning outcomes in the initial test of 21.42%. After taking action in cycle 1, the average score percentage increased to 67.85 %. And when the action was repeated in the second cycle, the percentage of students' average scores increased again to 89.28%. Meanwhile, in the analysis of data for classical learning completeness in the initial test, the percentage of classical learning students was only 21.42% and did not meet the set learning completeness standard, which was 70%. Meanwhile, in the second cycle after taking action, the percentage of classical learning completeness reached 89.28%. The conclusion is that the application of the project-based learning model assisted by animation video media can improve the learning outcomes of grade V students of SD Alkhairaat Tondo.